Antisense Drug Technology Principles, Strategies, and Applications - Crooke, Stanley T;Ed (CRC Press, 2008)
This second edition continues to offer answers to challenging questions while looking ahead to the future of antisense drugs, covering the fundamentals of oligonucleotide-based therapeutics and hybridization-based drugs as well as therapeutic applications for cardiovascular purposes, metabolic diseases, and cancer.